Enhancing electrochemical transistors based on polymer-wrapped (6,5) carbon nanotube networks with ethylene glycol side chains - Heimfarth, Daniel; Leinen, Merve; Klein, Patrick; Allard, Sybille; Scherf, Ullrich; Zaumseil, Jana (ACS applied materials & interfaces, 2022)
Organic electrochemical transistors (ECTs) are an important building block for bioelectronics. To promote the required ion transport through the active layer, state-of-the-art semiconducting polymers feature hydrophilic ethylene glycol side chains that increase the volumetric capacitance and transconductance of the devices. Here, we apply this concept to polymer-wrapped single-walled carbon nanotubes (SWCNTs) as a high-mobility semiconducting material. We replace the polyfluorene copolymer (PFO-BPy), which is used for selectively dispersing semiconducting (6,5) SWCNTs and contains octyl side chains, by an equivalent polymer with tetraethylene glycol side chains. Aerosol-jet printed networks of these SWCNTs are applied as the active layer in water-gated ECTs. These show high hole mobilities (3-15 cm2·V-1·s-1), significantly improved volumetric capacitances and larger transconductances. Thin networks of SWCNTs reach (219 ± 16) F·cm-1·V-1·s-1 as the product of mobility and volumetric capacitance. In situ photoluminescence measurements show more efficient quenching of the near-infrared fluorescence for nanotube networks with hydrophilic glycol side chains compared to those with hydrophobic alkyl side chains, thus corroborating more complete charging under bias. Overall, networks of semiconducting SWCNTs with such tailored wrapping polymers provide excellent device performance. Combined with their inherent mechanical flexibility and durability, they constitute a competitive material for bioelectronics.
Gesehen am 13.04.2022